TEACHING VOCABULARY TO YOUNG LEARNERS BY USING ANIMATION VIDEO - Lina Silfia; Tri Indah Rusli; Rahmat Nasrullah (Universitas Lambung Mangkurat, 2018)
This study is a classroom action research (CAR) on utilizing animation video in teaching vocabulary to young learners. Therefore, the objective of this study is to find whether the use of animation video can improve vocabulary mastery of grade IV students of SD Negeri 2 Baruga. This research is conducted within two cycles in which each cycle consisted of three meetings. Either first cycle or second cycle consisted of planning, action, observation/evaluation, and reflection. The subject of this study was students at grade IV of SD Negeri 2 Baruga. A number of the students in the class were 30 with 8 male and 22 female. Then, the instruments were used in this study include observation sheet of teacher’s and students’ activity, and vocabulary test. The researcher found that teaching English by using animation video can improve students’ vocabulary at grade IV of SD Negeri 2 Baruga. The improvement could be seen in the result of students’ achievement after conducting this study was 93 % proved that it achieved classical achievement. Moreover, percentage of teacher’s and student’s activity also achieved 82.14% and 68.70%. On other words, the students’ vocabulary at grade IV of SD Negeri 2 Baruga improved by using animation video.Keywords: Animation video, Vocabulary and Young Learner